Analisis Motivasi dan Disiplin Kerja dalam Meningkatkan Kinerja Karyawan pada Toko Besi Tiga Jaya Makmur - Defrizal; Musafi Aldilah (Jurnal EMT KITA, 2023)
This study aims to analyze work motivation and labor discipline in improving the work efficiency of workers at Tiga Jaya Makmur cast iron factory. In this study, two independent variables were tested, namely work motivation and work discipline. The population of this study included workers of the Tiga Jaya Makmur ironworks. The sources for this study are 1 owner and 4 employees. Qualitative analytical methods are performed using techniques of data reduction, data presentation, and conclusion or verification of research results. Research results analyzing work motivation and work discipline in improving employee performance at Tiga Jaya Makmur Ironworks, Bandar Lampung, conclude that work motivation and work discipline play a role important role in supporting employee performance. Employee performance at Tiga Jaya Makmur Iron Shop in Bandar Lampung can be considered good if employee performance is satisfactory and can improve the company's image well.